Risks associated with undirected use of hormonal anabolizers (Research, Society and Development, 2021)
Introduction: Testosterone, the so-called male hormone, is the most important androgen in the body. In men, most testosterone is produced in the testes by Leydigin cells. In women, testosterone levels are much lower than in men. However, it also has an important effect on the female body. Hormonal regulation of testosterone is maintained and controlled by the hypothalamic-pituitary-gonad axis. Objective: To demonstrate the risks associated with the unguided use of anabolic androgen steroids for muscle hypertrophy purposes. Methods: This is a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (Prism) technique. The bibliographic research was carried out in the following databases: Medline (via PubMed), Scientific Electronic Library Online (Scielo) and the Virtual Health Library (VHL), published between 2014 and 2021 with exploratory objectives and a qualitative approach. The following descriptors were used: anabolic androgenic steroids and testosterone, anabolic androgenic steroids and indiscriminate use, anabolic androgenic steroids and adverse effects, indiscriminate use and testosterone, adverse effects and testosterone. Results: Initially, 56 studies were selected in the PUBMED, Scielo and BVS databases, after a more detailed reading, 9 articles used in this article were chosen. As a result of long-term androgen use, the testes can be significantly reduced. Conclusions: The negative effects of the use of anabolic steroids do not disappear completely after discontinuing their use, among the undesirable effects such as the risk of cardiovascular diseases, masculinity in women, muscle hypertrophy and liver damage, among others.